2021
DOI: 10.1111/scd.12607
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of silver diamine fluoride and glass ionomer cement combined with fluoride varnish in arresting dental caries among intellectually disabled individuals: A randomized controlled trial

Abstract: To assess the clinical effectiveness of 38% silver diamine fluoride (SDF) in arresting dental caries when compared to combination of fluoride-containing glass ionomer cement (GIC) and fluoride varnish(FV) (5%) among intellectually disabled (ID) individuals. Methodology: A randomized controlled trial was conducted among ID (n = 82) individuals, in permanent posterior teeth with Nyvad score 2 and 3 (active caries) of dental caries, randomly allocated to experimental arm (38% SDF) (n = 41) and control arm (GIC al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…The quality of the included studies rated between level II and lV. Three RCT (one of them has two entrances for different types of outcomes) ( 21 24 ), one pragmatic controlled clinical trial ( 25 ), one prospective cohort study ( 26 ), one retrospective audit ( 27 ), and four retrospective cohort studies ( 28 31 ) reported the outcomes of different interventions that aimed to restore teeth affected by caries disease in patients with disability in time interval 2011–2022.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of the included studies rated between level II and lV. Three RCT (one of them has two entrances for different types of outcomes) ( 21 24 ), one pragmatic controlled clinical trial ( 25 ), one prospective cohort study ( 26 ), one retrospective audit ( 27 ), and four retrospective cohort studies ( 28 31 ) reported the outcomes of different interventions that aimed to restore teeth affected by caries disease in patients with disability in time interval 2011–2022.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the use of nonaerosol‐generating minimally invasive procedures in clinical dental care is increasing. For all these reasons, there is a clear need to find effective, safe, and accessible alternatives for the treatment of caries lesions in these groups of patients (Crystal & Niederman, 2019 ; Gao et al, 2021 ; Mendiratta et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of patients with SHCNs aged 0−18 years who present <3 caries lesions, if there is no pain, the choice of treatment will depend on the patient's ability to cooperate. In uncooperative children, we opt for simpler strategies such as SDF or SMART (Crystal et al, 2017 ; Mendiratta et al, 2021 ), while in those able to cooperate, the conventional treatment indicated in each case will be carried out at the hospital's outpatient clinics. Patients in this same group who present four or more carious lesions without painful symptoms undergo comprehensive treatment under GA.…”
Section: Discussionmentioning
confidence: 99%
“…13 Mendiratta ve ark. 14 mental retarde çocuklarda yaptıkları randomize kontrollü bir çalışmada, bir gruba sadece bir kez GDF uygulamışlar, diğer gruba ise atravmatik restoratif tedavi ile kombine olarak florürlü vernik uygulamışlardır. Her iki uygulamanın çürük durdurma etkinliğinin benzer nitelikte olduğunu belirtmişlerdir.…”
unclassified
“…Her iki uygulamanın çürük durdurma etkinliğinin benzer nitelikte olduğunu belirtmişlerdir. 14 Çürüğü durdurmak için uygulama sayısı ve sıklığı konusunda fikir birliği yoktur. Çocuklarda kullanım şekline ilişkin kanıta dayalı kılavuzlar geliştirmek için daha ileri çalışmalar gereklidir.…”
unclassified